Thirst Modulates Parasympathetic Recovery: Comparing Oral and Intravenous Rehydration - Alan T. Ky; Ryan A. Dunn; Marcos S. Keefe; Yasuki Sekiguchi (Physiologia)
Introduction: Oral rehydration reduces thirst sensation (TS), which may negatively affect autonomic function, measured by heart-rate variability (HRV). However, it is unclear if this effect is independent of hydration changes. This study examines whether TS influences autonomic function between intravenous and oral rehydration. Methods: Twelve males (mean ± SD; age, 29 ± 12 years; 74.7 ± 7.9 kg; 179.4 ± 7.0 cm; VO2max, 49.8± 6.6 mL·kg−1·min−1) cycled at 55% VO2max for 90 min followed by a 12 km time trial. Two experimental conditions were performed in a counterbalanced, randomized order; (a) the high thirst (HT) group were infused 25 mL of isotonic saline every 5 min via an intravenous tube, and (b) the low thirst (LT) group ingested 25 mL of water every 5 min. TS and heart rate were collected every 5 min. HRV was assessed pre exercise, post steady-state exercise, and post time trial. HRV parameters included time domain, frequency domain, and non-linear measures analyzed by two-way repeated measures ANOVA. Results: There was a significant time x condition for the root mean square of successive RR interval differences (RMSSDlog), high-frequency (HF) power, and SD1 (p < 0.05). In LT, RMSSDlog decreased from Pre to Mid (3.71 ± 0.61 ms to 2.53 ± 1.15 ms, p < 0.01) and Pre to Post (2.18 ± 0.90 ms, p < 0.01) but stabilized from Mid to Post (p = 0.39). High-frequency (HF) power in HT was maintained from Pre (3.7 ± 0.6 nu) to Mid (3.4 ± 0.8 nu, p = 0.21) but decreased from Pre to Post (2.5 ± 0.7 nu, p < 0.01) and Mid to Post (p < 0.01). LT decreased in HF power from Pre (3.7 ± 0.5 nu) to Mid (3.0 ± 0.8 nu, p < 0.01) and Pre to Post (3.0 ± 0.7 nu, p < 0.01); Mid and Post was maintained (p = 0.99). SD1, decreased in HT (Pre: 3.4 ± 0.4 ms, Mid: 2.0 ± 1.1 ms, Post: 1.1 ± 0.5 ms; all comparisons p < 0.05). In LT, SD1 decreased from Pre (3.4 ± 0.6 ms) to Mid (2.18 ± 1.15 ms, p < 0.01) and Pre to Post (1.83 ± 0.90 ms, p < 0.01), but stabilized Mid to Post (p = 0.39). Conclusion: Satiating thirst through oral rehydration increases parasympathetic activity post exercise, reducing stress and increasing recovery between exercise bouts. These findings have implications for optimizing rehydration strategies in sports and occupational settings.